Control of Clove Plant Disturbing Organisms in Amerta Masa Farmer Group in Asahduren Village, Pekutatan District, Jembrana Regency - A. A. S. Putri Risa Andriani; A.A.Ngurah Mayun Wirajaya; Ida Bagus Komang Mahardika; Luh Kartini; I Gusti Made Arjana; Yohanes Parlindungan Situmeang; I Nengah Suaria; Made Sri Yuliartini; Ketut Agung Sudewa; Ni Komang Alit Astiari; I Gusti Bagus Udayana; Sandra Pakusi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Amerta Masa Farmer Group is a farmer group in Asah Duren Village that focuses on cultivating cloves. The problem faced by the Amerta Masa Farmer Group is the lack of knowledge about the control techniques of Clove Plant Disturbing Organisms. Control using root infusion techniques is very effective, efficient and more selective, but this method requires expertise or trained personnel so that in its implementation there is no difficulty in obtaining roots suitable for this application. Therefore, the service team provides assistance and direct practice in overcoming the problem of controlling organisms that disturb clove plants. After the implementation of the activity, it was obtained that, partners have been able to practice controlling organisms disturbing clove plants so as to increase production by 10-20%. Mitra hopes to get continuous assistance in cultivating cloves so that they can remind the production of clove plants.